STUDI EMPIRIS KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Saleh, Rachmad; Susilowati, lndah (JURNAL BISNIS STRATEGI, 2004)
The study aims to investigate firms' compliance in reporting the annual financial report to the BAPEPAM. Respondents were selected from the manufacture firms listed in Jakarta Stock Exchange. Hundred and ten firms sampled out of 155 firms (population) were withdrawn from annualy data of 2000-2002. The estimation technique of PROBIT model was invoked to analyze the data by using SHAZAM as econometrics' package (White, 1997). Two scenarios of Probit model were run to find out the best fit model. The results indicated that extraordinary and/or contingent items (EXTRA) variable was significant at a = 5 % to influence the firms' compliance (Timeliness) in submetting their annual financial report. While gearing (GEAR), profitability (PROFIT), size of firm (SIZE), age of firm (AGE) and ownership (OWN) have not statistically able to determine the dependent variable of compliance (Timeliness).This study suggests that the firm's compliance to submit the annual financial report on time should be measured more precisely to allow for indepthed resulst. Moreover, the aspects of auditor, the complexity of firm, types of audit committee and the quality of firm internal control have accounted for the future research.